Implementation of Arduino-Based Line Follower Robotics Technology for Practical Automation Learning at SMK Negeri 1 Kaliwungu - Muhammad Hassan Massaty; Slamet Kurniawan Fahrurozi; Cucuk Wawan Budiyanto (DEDIKASI: Community Service Reports, 2025)
The application of Arduino-based robotics technology in vocational education has received significant attention as a practical learning method, especially in fostering automation skills. This community service focuses on the development and implementation of a line follower robot project at SMK Negeri 1 Kaliwungu to support practical learning in the automotive engineering program. This project introduces students to the basic concepts of automation through hands-on experience in microcontroller programming, sensor integration, and electronic circuit design using the Arduino platform. This community service adopts a project-based learning approach, involving students in designing, building, and testing a line follower robot. This method aims to bridge theoretical knowledge and practical applications, equipping students with skills that are in line with industry demands. The implementation is carried out in a structured learning environment supported by adequate facilities and modern tools to simulate real-world scenarios. The practical results show that students show significant improvements in their understanding of automation systems, problem-solving abilities, and technical skills relevant to robotics and automotive applications. Furthermore, the project-based approach encourages collaborative teamwork and independent learning, preparing students to face the challenges of a rapidly evolving technological landscape. This service highlights the potential of integrating Arduino-based robotics into vocational school curricula as a medium to enhance practical skills and technological literacy. It also provides a replicable framework for other institutions looking to incorporate automation technology into their educational programs.